Improved follow-up of patients with differentiated thyroid carcinoma - Dießl, S.; Verburg, F.; Biko, J.; Schryen, B.; Reiners, C.; Buck, A.; Hänscheid, H. (Nuklearmedizin - NuclearMedicine, 2013)
Aim: Physicians typically are unaware of the radioiodine uptake (RIU) detection limit (LoD) on scintigrams of differentiated thyroid carcinoma (DTC) patients. We evaluated a novel method to determine LoD as a quantitative upper limit for RIU in negative scans and as a value to contextualize faint visible uptake. Patients, methods: To test whether LoD is related to physicians’ ratings, RIU and LoD were calculated from scintigraphic count statistics for 120 static planar neck scans and were compared with the ratings of five nuclear medicine specialists blinded to patient/ scan characteristics regarding visible cervical uptake. Scans were acquired on days 1 (d1) and 2 (d2) post-administration of 298 ± 30 MBq iodine-131 in 60 consecutive DTC patients after recombinant human thyrotropin (rhTSH) or thyroid hormone withdrawal (THW) (n = 30 each). Results: Indicating good inter-observer agreement, ≥ 4 readers concurred regarding 56 (93.3%) [54 (90.0%)] d1[d2] scans. Seventeen scans from 12 patients received ≥ 3 positive votes; in 15 (88.2%), RIU exceeded LoD. RIU assessed from regions-of-interest over former thyroid beds in scans with ≤ 2 positive votes was typically below the LoD (99/103 scans, 96.1%). In 48 patients with ≤ 2 positive votes in both scans, LoD was a median 0.0094% (0.0050%) in d1(d2) images and was significantly lower (p < 0.01) on early or late scans in 22 euthyroid rhTSH patients versus 26 hypo thyroid THW patients. Conclusion: LoD data obtained by the proposed method closely reflect nuclear medicine specialists’ scan ratings and provide comparators in serial scintigrams, improving diagnostic 131I imaging accuracy in differentiated thyroid carcinoma.
Keywords: Thyroid carcinoma; 131I uptake; radioiodine; diagnostic scan; scintigraphy; quantitative detection limits